Pengaruh Motivasi Kerja dan Gaya Kepemimpinan terhadap Kinerja Pegawai PT Jasa Raharja Cabang Sumatera Utara - Evelyn Br Hutagalung; Indra Siregar; Suriyadi Suriyadi; Nursiah Fitri; John Sihar Manurung (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2024)
In the context of Human Resource Management (HRM), two aspects that play a key role in shaping employee performance are motivation and leadership style. This study aims to analyze the influence of work motivation and leadership style on employee performance at PT Jasa Raharja North Sumatra Branch. Data was collected from 40 respondents using a saturated sample and analyzed using multiple linear regression. The method used in this research is quantitative method with regression analysis technique. The results of the study show that work motivation (X1) has a significant partial effect on employee performance (Y), with a significance value of 0.001 < 0.05 and a calculated value > t table value, which is 3.520 > 2.02619. Conversely, leadership style (X2) has no significant partial effect on employee performance, with a significance value of 0.893 > 0.05 and a calculated value < t table value, which is 0.135 < 2.02619. However, simultaneously, work motivation and leadership style have a positive and significant effect on employee performance with a calculated F value (14.484) > F table value (3.24) and a significance value (0.000) < (0.05). The regression analysis shows that the regression coefficient X1 is 0.496, indicating that work motivation has a positive effect on employee performance, while the regression coefficient X2 is 0.017, indicating that leadership style also has a positive effect on employee performance, although not significant when considered partially. The R square value of 0.439 shows that 43.9% of the variation in employee performance can be explained by work motivation and leadership style, while the remaining 56.1% is influenced by other factors not examined. This study concludes that both work motivation and leadership style together improve employee performance at PT Jasa Raharja North Sumatra Branch.